Tullia d’Aragona: Tidigmodern feministisk poet och kärleksfilosof - Vernqvist, Johanna (Tidskrift för litteraturvetenskap, 2020)
Tullia d’Aragona: Early Modern Feminist, Poet and Philosopher of Love This article gives an overview of the life and work of the early modern poet and philosopher Tullia d’Aragona, with specific focus on the feminist ideas that are presented in her dialogue on love, Dialogo della infinità di amore (1547). By extensively referencing classical and contemporary writers on the subjects of love and gender, like Plato, Marsilio Ficino and Sperone Speroni, Aragona places her Dialogo in the middle of the early modern debate on love and skillfully makes use of dialogical rhetoric in order to discuss and criticize existing configurations of love and gender. By considering the significance of the body, this article shows how the incorporated dismissal of women in for example Neoplatonic ideas where the (female) body is connected to base and lascivious love in opposition to the ennobling and honest love of (male) souls, is questioned, countered and re-written by d’Aragona.